Implementasi Program Manajemen Risiko Keamanan Pangan Bertahap pada Industri Pangan Steril Komersial di Yogyakarta - Tyas Setyaningsih; Wahyu Sulistiadi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Changes in consumer demand for convenient food have spurred the development of commercially sterile food products produced by micro and small enterprises (MSEs). However, commercially sterile food carries the risk of botulism, which can lead to illness or even death. This risk has prompted the government to issue an Indonesian Food and Drug Authority Regulation Number 10 of 2023, which outlines the implementation of the Food Safety Risk Management Program (RMP) in processed food production facilities. This regulation requires MSEs to adopt a phased RMP to ensure food safety. This research aims to assess the performance of RMP implementation among MSEs. A qualitative approach was used, incorporating data from in-depth interviews, observations, and document reviews. The results indicate that budgets, costs, and incentives were inadequate in terms of resources.